2002
DOI: 10.1055/s-2002-35530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salbutamol and Caffeine Ingestion on Exercise Metabolism and Performance

Abstract: This study was designed to assess the effects of acute oral salbutamol and caffeine intake on performance and metabolism during short-term endurance exercise. Eight healthy volunteers participated in the double-blind placebo-controlled randomized cross-over study. Two 10 min cycling trials were performed at a power corresponding to 90 % VO 2 max for the first and a mock test for the second, separated by 10 min of passive recovery after ingestion of placebo (Pla), salbutamol (Sal, 6 mg) and caffeine (Caf, 250 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
(54 reference statements)
6
26
0
2
Order By: Relevance
“…The earlier limited data on the effects of acute salbutamol on GH in humans (Giustina et al 1995;Collomp et al 2005;Le Panse et al 2006) have found acute salbutamol administration to decrease exercise GH concentrations, probably via enhanced somatostatin secretion and/or activity. In healthy subjects, acute b 2 stimulation blunts the physiological GH response to both maximal (Collomp et al 2002) and supramaximal exercise (Le Panse et al 2007). It may than be suggested that a higher intensity of exercise is necessary to reveal a blunted effect of acute salbutamol on GH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The earlier limited data on the effects of acute salbutamol on GH in humans (Giustina et al 1995;Collomp et al 2005;Le Panse et al 2006) have found acute salbutamol administration to decrease exercise GH concentrations, probably via enhanced somatostatin secretion and/or activity. In healthy subjects, acute b 2 stimulation blunts the physiological GH response to both maximal (Collomp et al 2002) and supramaximal exercise (Le Panse et al 2007). It may than be suggested that a higher intensity of exercise is necessary to reveal a blunted effect of acute salbutamol on GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, only two studies (Collomp et al 2000a(Collomp et al , 2002 investigated these parameters and showed that systemic salbutamol intake increases Cpeptide or insulin concentrations without significant change in blood glucose concentrations during 80-85% VO 2 max submaximal exercise or a mock test. In the present work, we did not find any significant change in either blood glucose or insulin concentrations after salbutamol intake compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three peer-reviewed research articles met the inclusion criteria (Alves et al, 1995;Bell, Jacobs, & Zamecnik, 1998;Berglund & Hemmingsson, 1982;Bridge & Jones, 2006;Butts & Crowell, 1985;Cadarette, Levine, Berube, Posner, & Evans, 1983;Cha et al, 2001;Cohen et al, 1996;Collomp et al, 2002;Conway, Orr, & Stannard, 2003;Costill et al, 1978;Denadai & Denadai, 1998;French et al, 1991;Fulco et al, 1994;Graham, Hibbert, & Sathasivam, 1998;Graham & Spriet, 1991;Greer, Hudson, Ross, & Graham, 2001;Ivy et al, 1979;Jenkins, Trilk, Singhal, O'Conner, & Cureton, 2008;Lindinger, Graham, & Spriet, 1993;MacIntosh & Wright, 1995;McLellan, Bell, & Kamimori, 2004;McNaughton et al, 2008;Norager, Jensen, Madsen, & Laurberg, 2005;Pasman et al, 1995;Powers, Byrd, Tulley, & Callendar, 1983;Sasaki et al, 1987;Slivka et al, 2008;Spriet et al, 1992;Trice & Haymes, 1995;Van Soeren & Graham, 1998; Table 3). Three research articles Berglund & Hemmingsson, 1982;Butts & Crowell, 1985) reported Note.…”
Section: Study Characteristics For Caf Versus Placebo Analysismentioning
confidence: 99%
“…On the other hand, others (Haller et al, 2004;Collomp et al, 2002) narrate no significant difference in lactate concentration in association with caffeine use. The belief diffused that intense exercise leads to "lactic acid" production, which contributes to acidosis, is questionable.…”
Section: Introductionmentioning
confidence: 93%